PENGARUH KEPUASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BANK DI KOTA BATAM - Rizki Novriyanti Zahara; Hajan Hidayat (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
This study aims to identify and analyze the influence of job satisfaction and work discipline on employee performance. Approach method used for sampling is purposive sampling technique. Respondents were used in this study were 173 employees working in state-owned banks in Batam. This study uses regression analysis to examine how the influence of these two variables on the performance of employees with SPSS 22.0 application. Results of the t test obtained by value t count 3,979> t table 1,973, which means that H1 is accepted and t value 4,623> t table 1973, which means H2 is accepted. The higher the satisfaction is fulfilled and the higher discipline of work that employees have the higher the employee's performance. Based on the results of research conducted, it can be concluded that there is influence between the variables of job satisfaction and work discipline on employee performance state-owned banks in Batam. Keywords: Job satisfaction, Discipline, Employee Performance